Electrical Characterization of Zirconium Silicate Films Obtained from Novel MOCVD Precursors - Paskaleva, Albena; Lemberger, Martin; Zürcher, Stefan; Bauer, Anton; Frey, Lothar; Ryssel, Heiner (Proceedings of the 12th Workshop on Dielectrics in Microelectronics (WoDiM 2002), 2003)
In the present work, the potential of zirconium silicate (ZrSixOy) films as an alternative gate dielectric to SiO2 for future technology generations is demonstrated. Novel single-source precursors for MOCVD of zirconium silicate were synthesized and ZrSixOy layers were deposited. I-V and C-V measurement data are presented and detected charge trapping phenomena are discussed. © 2003 Elsevier Ltd. All Rights Reserved.
UnivIS-Import:2017-07-10:Pub.2003.tech.IE.LEB.electr_0